High Throughput Screening for Bioactive Components of Berberis baluchistanica Ahrendt Root and Their Functional Potential Assessment. (26th July 2022) - Gul, Zareen; Akbar, Ali; Ali, Imran; Muhammad, Javed; Rehman, Zia Ur; Bano, Amna; Samad, Abdul; Khan, Amjad; Samiullah; Leghari, Saadullah Khan; Chein, Su Hlaing; Rabaan, Ali A.
Abstract : Berberis baluchistanica Ahrendt is a medicinal plant potentially known for the treatment of different diseases. The bioactive, antioxidant, nutritional components, and antimicrobial properties of crude ethanolic root extract of Berberis baluchistanica were evaluated in this study. The extract was analyzed for total phenolic, flavonoid, DPPH (2, 2-diphenyl-1-picryl-hydrazyl) scavenging ability, FRAP (ferric reducing antioxidant power), nutritional, and antimicrobial potentials. The alkaloids, tannins, cardiac glycosides, anthraquinones, coumarin, saponins, phenolics, flavonoids, steroids, and terpenoids were confirmed. The extract possessed DPPH radical inhibition with the IC50 of 1.125 mg/mL and FRAP % reduction activity with IC50 (0.912 mg/mL). Total phenolic 19.897 ± 4.8141 mg GAE/g and flavonoid 12.9876 ± 0.8388 mg QE/g contents were confirmed in the root. The extracts exhibit good antibacterial activity against a broad spectrum of food borne pathogens Pseudomonas aeruginosa, Salmonella typhi, Klebsiella pneumoniae, Escherichia coli, and Staphylococcus aureus . The highest inhibitory activity was against Escherichia coli 23.30 ± 1.16 mm and lowest against Klebsiella pneumoniae 7 ± 0.01 mm . Furthermore, the presence of various phytochemical constituents (plant secondary metabolites) was also confirmed with gas chromatography and mass spectroscopy analysis. Results disclosed the occurrence of more than 70 compounds possessing various medicinal properties supporting the traditional uses of root of Berberis baluchistanica in various medical complications indigenously.